PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ANALISIS ABC (STUDI KASUS PADA PERUSAHAAN INTERIOR DESIGN “XYZ” KARAWANG) - Savira, Arsylla Dinda; Miharja, Rediawan (Unitri Press, 2024)
The purpose of this study is to aim to determine the classification or types of raw materials which include groups A, B, and C which are expected to help companies in selecting and classifying which types of raw material components are more important than other raw material components and controlling these raw materials. This research technique uses descriptive research with a quantitative approach. Based on the results of data processing, the raw materials can be classified into 3 classes, namely: class A, class B and class C. Of the 12 types of raw materials calculated, those included in class A amounted to 3 types of components, namely multiplek, blobkboard and HPL with a percentage value of the annual volume of rupiah of 63.55%, while for class B there are 4 types of components, namely PVC board, vinyl floor, paint duco and accessories with a percentage value of the annual volume of rupiah of 35.12% and the last is class C which consists of 5 types of components, namely nails, glue, couplers, taco sheet and edging with a percentage value of the annual volume of rupiah of 1.33% of the total annual volume of raw material rupiah.